An analysis of food demand in a fragile and insecure country: Somalia as a case study. (May 2021) - Hussein, Mohamud; Law, Cherry; Fraser, Iain
Highlights: We undertake the first formal estimation of food demand in Somalia. We present a range of elasticities by food group and household type. We examine issues around data collection in a fragile and insecure country. Implications for food security are examined. Abstract: We present an analysis of household level food demand for Somalia, which is emerging from a destructive twenty-year civil war. Using novel World Bank household survey data collected in 2018, we estimate demand elasticities for Somalia taking account of differences in household type, regional conflict, and income remittances from overseas. Our results reveal the extent to which household food consumption, as represented by expenditure, own and cross price elasticities, is highly sensitive to income shocks, especially for animal products such as meat and milk which are the main sources of protein for the population. Furthermore, the impact of an exogenous income shock, affecting food prices and household budgets, will likely result in a less diversified diet because of more emphasis on cereal consumption, especially for nomadic households. The resulting negative macronutrient implications have obvious consequences for levels of malnutrition. As such, improved food security is critical for Somalia's economic recovery and resilience in the future.